RELATIONSHIP BETWEEN PLANT OCCURRENCES AND SURFACE CONDITIONS ON A RECENTLY DEGLACIATED MORAINE AT NY-ÅLESUND, SVALBARD, ARCTIC NORWAY (19th Symposium on Polar Biology) - オキツ, ススム; ミナミ, ヨシノリ; カンダ, ヒロシ; OKITSU, Susumu; MINAMI, Yoshinori; KANDA, Hiroshi (National Institute of Polar Research, 1998)
P(論文) The relationship between plant occurrence and moraine surface conditions was studied in three areas along a deglaciated moraine (upper, middle and lower stream area from the glacier edge) in front of Brogger glacier in Ny-Ålesund, Spitsbergen, Svalbard The total number of species in an area and the mean number of species in a plot (3×3 m) increased from the upper to the lower stream. Plants occurred according to a chronosequence following glacier retreat. The occurrence pattern of species within an area shows two types, a few common species and many remaining sporadic ones, suggesting haphazard establishment of plants within an area. Plots with high fine-textured material cover tended to have more species than plots with low fine-textured material cover in all three areas, suggesting that fine-textured material promoted the plant occurrence. In the upper stream plants occurred only on plots with high fine-textured material cover, while in the lower stream plants sometimes occurred on plots with low fine-textured material cover. The mean rock size at a stand also affects the plant occurrence in the upper and middle stream, although it showed rather negative correlation to the number of species in the lower stream. departmental bulletin paper